2016
DOI: 10.4103/0974-2069.181495
|View full text |Cite
|
Sign up to set email alerts
|

Association between vitamin D levels and left ventricular function and NT-proBNP levels among thalassemia major children with iron overload

Abstract: Background:Heart disease is the major cause of death in thalassemia patients. Repeated blood transfusions and hemolysis cause iron overload and also disrupts the hydroxylation and synthesis of vitamin D, causing vitamin D deficiency. Vitamin D deficiency is associated with cardiac dysfunction.Objective:The purpose of this study was to determine the association between vitamin D levels and left ventricular function and N-terminal pro-brain natriuretic peptide (NT-proBNP) levels in thalassemia major children wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 26 publications
1
6
0
Order By: Relevance
“…The role of vitamin D and NT-pro BNP levels in thalassemic children and their correlation with LV functions were reported by Ambarwati et al 15 from Indonesia. The study reported significant negative correlation among serum levels vitamin D and LVEF (left ventricular ejection fraction) similar outcomes were also noted in the present study.…”
Section: Wwwtheprofesionalcommentioning
confidence: 70%
“…The role of vitamin D and NT-pro BNP levels in thalassemic children and their correlation with LV functions were reported by Ambarwati et al 15 from Indonesia. The study reported significant negative correlation among serum levels vitamin D and LVEF (left ventricular ejection fraction) similar outcomes were also noted in the present study.…”
Section: Wwwtheprofesionalcommentioning
confidence: 70%
“…Iron deposition in the liver might disrupt the hydroxylation of vitamin D in 25-OHD before the next hydroxylation in the kidneys in 1,25 OH 2 D 3 . Moreover, its deposition in the skin might affect vitamin D level due to disrupting vitamin D synthesis [ 62 ].…”
Section: Resultsmentioning
confidence: 99%
“…The fact that transfusion-dependent thalassemia was more prone to bacterial infection supports the alteration of immune function in this genetic disease [ 64 ]. The correlation of vitamin D deficiency in β-thalassemia has been known to alter the cardiovascular system [ 62 , 65 ], endocrines [ 66 ] and the bone [ 15 , 67 ]. A study involving all types of thalassemia, including β-thalassemia, supplementation of 50,000 IU of ergocalciferol (vitamin D 2 ) could increase the 25-OHD level; however, the effect of this supplementation on the immune system was not investigated [ 61 ].…”
Section: Resultsmentioning
confidence: 99%
“…Ambarwati et al reported that N-terminal pro-brain natriuretic peptide levels, which can be used to diagnose preclinical cardiac dysfunction, were higher in thalassemia major children with vitamin D de ciency than those with normal vitamin D levels. They also stated that thalassemic patients with cardiac dysfunction in conventional echocardiography have signi cantly lower vitamin D levels [23].…”
Section: Discussionmentioning
confidence: 99%